Efektivitas TikTok dalam Meningkatkan Personal Branding: Studi pada Mahasiswa KPI UIN Syahada Padangsidimpuan - Hasibuan, Irna Amelia; Dianto, Icol; Siregar, Nurfitriani M. (Kediri Journal of Journalism and Digital Media (KJOURDIA), 2025)
The emergence of TikTok social media can be used as a tool to improve personal branding. Although many students use this application, not all use it to build personal branding. This study aims to analyze the effectiveness of the use of TikTok social media and strategies in improving the personal branding of students of the Islamic Communication and Broadcasting Study Program, Syekh Ali Hasan Ahmad Addary Islamic State University, Padangsidimpuan. The method used in this study is qualitative descriptive with the theory of personal branding self prasentation from Tom Peters as the knife of analysis. The results of this study found that the use of TikTok social media is still not effective in building personal branding by students and the tendency to use TikTok without the right strategy. The significance of this finding indicates that TikTok is not used to build personal branding of students that matches the profile of their graduates, only 13 out of 45 informants are active in creating personal branding content that is in accordance with the profile of graduates. This study recommends the importance of strengthening the skills of students of the Islamic Communication and Broadcasting Study Program, Syekh Ali Hasan Ahmad Addary Islamic State University, Padangsidimpuan to manage TikTok social media through the content of practicum courses and practices directly in the laboratory.